Implementasi Model Pembelajaran Grup Investigasi Secara Daring pada Mata Kuliah Pendidikan Kewarganegaraan di Masa New Normal - Dewi Maskulin; A. Rosyid Al Atok; Umi Dayati (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The online investigation group learning model is a learning model that can direct students to be sensitive to problems in the surrounding environment and be able to adapt to technological developments, especially in the new normal era like today. This study aims to determine the applicability of the online investigative grub learning model. The method used in this study uses the ADDIE development method which has five stages in the form of (1) analysis, (2) design, (3) development, (4) implementation and (5) evaluation. Trials of the online investigation group learning model were carried out by analyzing and categorizing student learning outcomes. Based on the trial implementation of the online investigation grub learning model, it was found that this learning model was effective and could be used in the learning process of the Citizenship Education course.